De Normandie en Angleterre : enquête sur la poétique de trois rouleaux mortuaires - Monique Goullet (Tabularia)
From the early Middle Ages to the modern era, funeral rolls circulated within confraternity networks. Words of condolence (tituli) were collected by a roll carrier (rolliger) who went from door to door. Three rolls were selected here for their relationship with Norman and English areas: that of Bruno the Carthusian, which circulated in 1101-1103; that of Matilda, abbess of the Holy Trinity of Caen (1113-1114); that of Vitalis of Savigny (1123-1124). At that time and during the whole twelfth century, poetry was the most commun medium in these rolls. In every poem scansion has been made visible, so that the reader can perceive metrical and phonic schemes. These verses, improvised or written in advance, show a metric diversity, yet quantitative but already partly syllabic and rhythmic.